Chest pain as a diagnostic dilemma in community-acquired pneumonia – A clinical perspective - Ranjan Kumar Singh (Asian Journal of Medical Sciences, 2025)
Pneumonia that develops outside of health facility is called community-acquired pneumonia (CAP). A diagnosis of CAP requires the patient to present with leukocytosis, fever, dyspnea, cough, and other clinical syndromes, as well as an infiltrate seen upon chest imaging. The presenting complaint may be pleuritic chest alone. The severity of pneumonia is gauged on a 0–5 scale of CURB-65. In this clinical vignette, the CURB-65 score was 2, and the patient was admitted to the general ward with intravenous co-amoxiclav (1.2 g) thrice a day and oral levofloxacin (750 mg) once a day administered for 5 days. The patient was subsequently switched to oral co-amoxiclav (625 mg) three times a day along with levofloxacin for 5 additional days. The 2019 American Thoracic Society/Infectious Diseases Society of America suggests that the standard empiric therapy for inpatient care of CAP is beta-lactam/fluoroquinolones or beta-lactam/macrolides.